Uma an??lise das metodologias de gerenciamento de projetos em incubadoras de base tecnol??gica e parques tecnol??gicos no estado de S??o Paulo: um estudo de casos m??ltiplos - Souza, Edson Rezende de (2017)
The number of technology-based incubators and science parks is continuously growing every year in Brazil and in other countries and, therefore, it is important to analyze how these entities manage the companies that they house and that can be considered as their projects. Studies indicate that many incubated companies and residents leave the incubators and parks because of management failures of the entities as managers and of the incubated resident companies. Project Management (PM) is considered a strategic tool and, according to studies conducted on the subject, can provide considerable support to the Incubators on the management of the incubated companies since your admission until your graduation, and for the technological parks that will house many of the technology companies that have left the incubators and will solidify its operations for further entry into domestic and international markets. Thus, this study proposed to analyze how IBTs and technology parks manage their projects in a point of view of traditional and agile Project Management methodologies. To this end, this study has adopted a qualitative research design with exploratory and descriptive approach using the methodology of a multiple case study. The data collection was performed through semi-structured interviews with project managers in technology incubators and science parks located in the S??o Paulo State, Brazil. Among the findings, it was found adherence to use of more flexible GP methodologies on technology-based incubators, and more structured methods in the science parks. The main theoretical contribution of this study was opening new horizons for new researches related to GP used in incubators and science parks. In a practical context, it was possible to submit to incubators structured arguments about the importance of adopting, and applying the PM practices in the selection and conduction of incubated firms towards your graduation. In the case of science parks, the practice is dedicated to the use of structured selection methods of PM and to the monitoring of the firms that they house, as well as to disseminate such practices with technology-based firms that they support.